2021
DOI: 10.1038/s41598-020-80072-z
|View full text |Cite
|
Sign up to set email alerts
|

Dermal fibroblasts cultured from donors with type 2 diabetes mellitus retain an epigenetic memory associated with poor wound healing responses

Abstract: The prevalence of Type 2 diabetes mellitus (T2DM) is escalating globally. Patients suffer from multiple complications including the development of chronic wounds that can lead to amputation. These wounds are characterised by an inflammatory environment including elevated tumour necrosis factor alpha (TNF-α). Dermal fibroblasts (DF) are critical for effective wound healing, so we sought to establish whether there were any differences in DF cultured from T2DM donors or those without diabetes (ND-DF). ND- and T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 61 publications
(72 reference statements)
2
23
0
Order By: Relevance
“…Therefore, CXCL12 might probably be involved in the GDM pathophysiologically due to its association with angiogenesis. This is consistent with a previous study, which reported a close relationship between angiogeneic chemokines, such as CXCL1 and CXCL12, and endothelium damage and IR (69).…”
Section: Therapeutic Implicationssupporting
confidence: 94%
“…Therefore, CXCL12 might probably be involved in the GDM pathophysiologically due to its association with angiogenesis. This is consistent with a previous study, which reported a close relationship between angiogeneic chemokines, such as CXCL1 and CXCL12, and endothelium damage and IR (69).…”
Section: Therapeutic Implicationssupporting
confidence: 94%
“… 4 In addition, diabetes can interrupt normal wound healing via prolonged inflammation, impaired angiogenesis, and compromised epithelialization. 12 In this case, the patient had type 2 diabetes mellitus and received intraoperative radiotherapy. Consequently, he experienced a pelvic abscess on POD 5 and abdominal fistula on POD 33.…”
Section: Discussionmentioning
confidence: 94%
“…Cytokines such as TNF-α exhibit a negative effect on the healing process [52]. The increased production of TNF-α signifies prolonged inflammation, and once the dermis fibroblasts are destroyed, collagen and ECM production will stop [53]. In Diagram (B), the fibroblasts become senescent, reduce in numbers, inhibit migration to the wounded site, and alter collagen synthesis.…”
Section: Pathophysiology Of Chronic Wounds and Diabetic Foot Ulcersmentioning
confidence: 99%